Genome Editing of eIF4E1 in Tomato Confers Resistance to Pepper Mottle Virus - Yoon, Yoo-Joung; Venkatesh, Jelli; Lee, Joung-Ho; Kim, Jinhee; Lee, Hye-Eun; Kim, Do-Sun; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2020)
Many of the recessive virus-resistance genes in plants encode eukaryotic translation initiation factors (eIFs), including eIF4E, eIF4G and related proteins. Notably, eIF4E and its isoform eIF(iso)4E are pivotal for viral infection and act as recessive resistance genes against various potyviruses in a wide range of plants. In this study, we used Clustered Regularly Interspaced Palindromic Repeats/CRISPR-associated protein 9 (CRISPR/Cas9)-mediated targeted mutagenesis to test whether novel sequence-specific mutations at eIF4E1 in Solanum lycopersicum (tomato) cv. Micro-Tom could confer enhanced resistance to potyviruses. This approach produced heritable homozygous mutations in the transgene-free E1 generation. Sequence analysis of eIF4E1 from E0 transgenic plants expressing Cas9 and eIF4E-sgRNA transcripts identified chimeric deletions ranging from 11 to 43 bp. Genotype analysis of the eIF4E1-edited lines in E0, E1, and E2 transgenic tomato plants showed that the mutations were transmitted to subsequent generations. When homozygous mutant lines were tested for resistance to potyviruses, they exhibited no resistance to tobacco etch virus (TEV). Notably, however, several mutant lines showed no accumulation of viral particles upon infection with pepper mottle virus (PepMoV). These results indicate that site-specific mutation of tomato eIF4E1 successfully conferred enhanced resistance to PepMoV. Thus, this study, demonstrate the feasibility of the use of CRISPR/Cas9 approach to accelerate breeding for trait improvement in tomato plants.